Vibrational Assignments, First-Order Hyperpolarizability and Molecular Structure of 5-(2-Chlorphenyl)-7-nitro-2,3-dihydro-1,4-benzodiazepine-2-one by Hartree-Fock and Density Functional Theory Calculations - Prasath, M.; Muthu, S. (Asian Journal of Chemistry, 2013)
Vibrational analysis of the 5-(2-chlorphenyl)-7-nitro-2,3-dihydro-1,4-benzodiazepin-2-one (5C7NB2) compound was carried out by using FT-Raman and FT-IR spectroscopic techniques. The equilibrium geometry, various bonding features and harmonic vibrational frequencies of 5C7NB2 have been investigated by Hartree-Fock (HF) and density functional B3LYP methods with the 6-31G (d,p) basis set. The geometry and normal modes of vibration obtained from the HF and DFT methods are in good agreement with the experimental data. The first order hyperpolarizability (b total) of this novel compound and related properties (b, μ and Da) are calculated using HF/6-31G (d,p) and B3LYP/6-31G(d,p) methods based on the finite-field approach.